Technical problems of industrial buildings adaptation : case study : "Artist's alley" in Zielona Góra - Nowogońska, Beata (Array, 2020)
The adaptation of post-industrial building allows for solving problems connected with the protection of relics and is useful in the process of providing order to the cultural landscape. However, the adaptation of historic buildings is associated with many problems. At the same time, the conservation, architectural, construction, technological requirements and the investor's ideas must be met. Meeting all conditions at the same time is a difficult task, but possible. The change in the way that a historic building is used requires a series of preliminary studies of the building to be carried out. The article presents the results of the diagnosis of the technical conditions preceding the adaption of a former factory in Zielona Góra.